Drivers of rodent community structure in an Urban National Park, Kenya - Immaculate M. Mungai; Nathan Gichuki; Dorcus A.O. Sigana; Benard Agwanda; Patrick Chiyo; Vincent Obanda; Olivia Wesula Lwande (PLoS ONE, 2025)
Nairobi National Park (NNP) is among Kenya’s most vulnerable ecosystems, experiencing significant pressure from urbanization. Rodents, which are sensitive to environmental changes, are considered bioindicators of ecosystem health, and their population dynamics can be used to assess ecosystem pressures such as urbanization. This study assessed the rodent community structure in NNP to understand the effects of various urban pressures by examining the relationships between rodent diversity, richness, and abundance with vegetation types and metrics, seasonality, and habitat disturbances. The capture-mark-release method was used to trap rodents from 15 sites in Nairobi National Park’s savannah, forest, and riverine vegetation types during the dry and wet seasons. The diversity, species richness and abundance were determined from the trappings. From 56 rodents trapped, five species were identified namely: Lemniscomys striatus, Hylomyscus sp, Rattus rattus, Mus mus and Otomys tropicalis. Rodent diversity at NNP was low (Simpson=0.7130; Shannon Weiner=1.40; Brillouin index=1.27) while Pielou’s species evenness, was moderate=0.44 indicating near equity in species distribution. Univariate Generalised linear models showed that rodent abundance was influenced by season, vegetation type, and vegetation metrics. The multivariate model indicated that rodents were more abundant in the wet season compared to the dry season, and that abundance was also positively associated with increased tree and shrub densities. Rodent species richness was positively associated with higher tree density, while vegetation types influenced rodent species diversity. Rodent abundance was influenced by vegetation type, vegetation metrics (density and cover), and season. Human disturbance had no effect in both models. It was observed that the diverse anthropogenic activities occurring in NNP, do not significantly influence rodent abundance compared to the measured biotic and abiotic factors. This first rodent survey in this Park provides preliminary data for continued monitoring of this ecosystem.